Power of power politics : from classical realism to neotraditionalism - Vasquez, John A. (New York, 1998)
In this new and much-expanded edition of his classic study, John Vasquez examines the power of the power politics perspective to dominate inquiry, and evaluates its ability to provide accurate explanations of the fundamental forces underlying world politics. Part I of the book reprints the original 1983 text of The Power of Power Politics. It examines classical realism and quantitative international politics, providing an intellectual history of the discipline and an evaluation of statistical research guided by the realist paradigm. Part Il provides six new chapters covering neorealism, post-modernism, the neotraditional research program on balancing, Mearsheimer's analysis of multipolarity and institutionalism, the debate on the end of the Cold War, and neoliberalism. Through the use of comparative case studies these chapters analyze the extent to which the realist paradigm has been progressive (or degenerating), and empirically accurate, and the extent to which it remains a relevant and explana torily powerful theoretical approach for our current era.
Keywords: International relations-Research